Strategi Dalam Mencegah PHK Massal Di Industri Teknologi: Studi Kasus Spotify Technology S.A - Harmen, Hilma; Amelia, Rika; Zahira, Tira Al; Fahira, Diana; Adella, Reghina; Sihombing, Melati; Pangaribuan, Hawila Sabta; Siregar, Waidan Nur (Manajemen & Bisnis Jurnal, 2025)
Abstract. The technology industry faces major challenges in managing its workforce amid global economic uncertainty and rapid technological developments. Mass layoffs are a common strategy used to increase efficiency, such as what happened at Spotify Technology S.A. in 2023. This article aims to analyze the causes of mass layoffs at Spotify and identify strategies that can be implemented to prevent layoffs in the technology industry. Using a descriptive qualitative approach and secondary data analysis, this article finds that the main factors of layoffs at Spotify include the global economic slowdown, suboptimal investment in business expansion, and increased automation based on artificial intelligence. Alternatively, companies can implement strategies such as more efficient organizational restructuring, employee skill enhancement (upskilling and reskilling), diversification of revenue sources, work flexibility, and transparency in decision-making. By implementing these strategies, companies can maintain business stability without significantly sacrificing their workforce.